Mary Magdalene from The New Testament to the New Age and beyond - Lupieri, Edmondo, (Themes in Biblical Narrative;, 2019)
An international team of twenty scholars under Edmondo F. Lupieri's direction produced Mary Magdalene from the New Testament to the New Age and Beyond . While the historical figure of the Magdalene may be lost forever, the construction of her literary images and their transformations and adaptations over the centuries are a lively testimony to human creativity and faith. Different pictures of Mary travelled through time and space, from history to legend and mythology, crossed religious boundaries, going beyond the various Christianities, to become a "sign of contradiction" for many. This book describes a special case of biblical reception history, that of the New Testament figure of a woman whose presence at the side of Jesus has been disturbing for some, but proves to be inspiring for others.